Main Profile

At A Glance

Proof: A(log B) = log (B^A), log A - log B = log (A/B)

Learn more: http://www.khanacademy.org/video?v=yEAxG_D1HDwProofs of the logarithm properties: A(log B) = log (B^A) and log A - log B = log (A/B)
Length: 07:57

Contact

Questions about Proof: A(log B) = log (B^A), log A - log B = log (A/B)

Want more info about Proof: A(log B) = log (B^A), log A - log B = log (A/B)? Get free advice from education experts and Noodle community members.

  • Answer

Ask a New Question